2013
DOI: 10.1111/gcbb.12128
|View full text |Cite
|
Sign up to set email alerts
|

Soil and crop response to stover removal from rainfed and irrigated corn

Abstract: Excessive corn (Zea mays L.) stover removal for biofuel and other uses may adversely impact soil and crop production. We assessed the effects of stover removal at 0, 25, 50, 75, and 100% from continuous corn on water erosion, corn yield, and related soil properties during a 3-year study under irrigated and no-tillage management practice on a Ulysses silt loam at Colby, irrigated and strip till management practice on a Hugoton loam at Hugoton, and rainfed and no-tillage management practice on a Woodson silt loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 27 publications
5
67
2
1
Order By: Relevance
“…Reduced residue cover in baled and grazed plots may have also increased fluctuations in soil temperature. While we did not monitor changes in soil temperature in this study, another study in a similar region (western Kansas) found that residue removal >50% increased the soil temperature by about 2°C in spring (Kenney et al, 2015). The same study found that the amplitude of daytime and nighttime soil temperatures in plots with limited or no residue cover in winter and spring was larger than in plots with high residue cover.…”
Section: Soil Texture and Climatementioning
confidence: 59%
“…Reduced residue cover in baled and grazed plots may have also increased fluctuations in soil temperature. While we did not monitor changes in soil temperature in this study, another study in a similar region (western Kansas) found that residue removal >50% increased the soil temperature by about 2°C in spring (Kenney et al, 2015). The same study found that the amplitude of daytime and nighttime soil temperatures in plots with limited or no residue cover in winter and spring was larger than in plots with high residue cover.…”
Section: Soil Texture and Climatementioning
confidence: 59%
“…Under high stover harvest, NT had a Sq of <3 in the top layer and a Sq of >3 in the bottom layer for CP and NT, respectively. The Sq of >3 in the CP top layer suggests that risks of soil erosion are likely increased due to the absence of soil cover as shown by Kenney et al (2015). The Sq scores in CP and NT were influenced by corn stover harvest at both layers.…”
Section: Resultsmentioning
confidence: 93%
“…Several studies have shown that stover harvest can have negative impacts on near-surface soil structure and physical properties Lal, 2008, 2009b;Osborne et al, 2014;Jin et al, 2015). The impacts of stover harvest have generally been assessed through classical soil physical measurements, such as soil bulk density, penetration resistance, aggregate stability, percentage macroaggregation, aggregate tensile strength, infiltration, hydraulic conductivity, air permeability, and soil water retention (Karlen et al, 1994;Blanco-Canqui et al, 2006, 2009bMoebius-Clune et al, 2008;Kenney et al, 2015;Wegner et al, 2015). Those soil properties were chosen because of their indirect relationship to soil structure, but they require substantial methodological expertise and demand tedious sampling and sophisticated laboratory analyses .…”
mentioning
confidence: 99%
“…Varvel and Wilhelm (2008) suggested that a stover yield of 6.0 Mg ha À1 is required to maintain SOC levels in the western Corn Belt. Kenney et al (2013) assessed the effects of stover removal at 0, 25, 50, 75, and 100% from continuous corn on water erosion, corn yield, and related soil properties during a 3-year study under various management practices on different soil types in Kansas. They observed that stover removal at rates !50% enhanced grain yield but increased risks of water erosion and negatively affected soil water and temperature regimes in this region.…”
Section: Annual Harvestable Stover Supply and Its Effects On Soc Dynamentioning
confidence: 99%
“…However, excessive removal of stover could adversely impact soil fertility and productivity (Varvel and Wilhelm, 2008;Tan et al, 2012;Kenney et al, 2013). With an increasing demand for crop residue as biofuel feedstock, balancing residue harvest and nutrient budgets to achieve sustainable crop production and soil fertility is becoming increasingly important.…”
Section: Introductionmentioning
confidence: 99%